Entrepreneurship and State Intervention in Time of Pandemic - Hatada, Fernando; Gomes Lima Melo, Cinira; Cíntia Cárnio, Thaís (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2021)
enfrentamento à pandemia. A relevância dessa análise está na verificação das consequências que pode advir do descumprimento de obrigações contratuais, e nos possíveis efeitos da iminente crise econômica, ambos relacionados com as determinações estatais que afetaram a continuidade das atividades empresariais. This scientific article aims to demonstrate the impacts of the coronavirus pandemic on the daily lives of Brazilian companies, focusing on the impacts detected in contracts already set and in force during the dispersion of the mentioned disease, as well as in the crises generated by measures of social isolation to contain its spread. The study addresses the State’s intervention in economic and social activities as a policy to face the pandemic. This analysis’s relevance rests on the verification of the consequences that may result from the breach of contractual obligations and on the possible effects of the imminent economic crisis, both related to the state determinations that affected the continuity of business activities.